South Africa's Fees Must Fall: The Case of #UPrising in 2015. Issue 3 (2nd October 2019) - Nomvete, Sandla; Mashayamombe, John
ABSTRACT: Writing from a participant observation point of view with supplement of in-depth interviews, this article presents UPrising, a student-led movement that emerged at the University of Pretoria's Hatfield campus during the 2015 Fees Must Fall tuition fees protest. We examine its activities within UP's politically contested student space, in terms of recruitment, mobilisation and organisation of students. The article also traces how UPrising led protests on campus-specific issues and proposed tuition fees increase that had been proposed in 2014 for the 2016 academic year in conversation with broader student protests of 2015. We argue that UPrising led a successful student struggle through a non-partisan approach, effective use of social media and strategic leadership in a space with intense surveillance and fraught with partisan student politics that intersected with gender.